A Late Iron Age and Romano-British Site at Gale Common, North Yorkshire. Issue 1 (August 2014) - Randerson, M. J.; Watson, J. E.; Graham, D. J.
<x content-type="archive" xml:space="preserve">Abstract</x> A late Iron Age to late Romano-British rural landscape centred on two core occupation areas was identified. The western settlement, in the form of a nucleated Iron Age farmstead, was inhabited in the first century bc, while the eastern core was occupied from the late first century ad. Settlement was predominantly at a basic rural level, shifting eastwards during the later second century ad to a less regular settlement with a rectilinear field system. The settlement became more Romanised, incorporating in the middle of the fourth century ad a rectangular timber building and proportions of pottery types more usually associated with villas. The settlement appears to either move, contract, or begin to dissipate in the later fourth century ad.